PENGARUH PROGRAM PENGENALAN LAPANGAN SATUAN PENDIDIKAN (PPLSP) DAN MINAT MAHASISWA TERHADAP KESIAPAN MENJADI GURU :Studi Pada Mahasiswa Program Studi Pendidikan Manajemen Perkantoran Angkatan 2017 Dan 2018 - Mega Nabilah Ainun Nada, - (2022)
This research was conducted by raising the problem that there are many students who are still not ready to become an educator or teacher. This is what motivated the author to conduct research. The focus of the study is on the factors that influence the readiness to become a teacher where the Program Pengenalan Lapangan Satuan Pendidikan (PPLSP) and student interest are factors that are thought to have an influence on readiness to become a teacher. This study aims to determine the description of PPLSP, student interest, and readiness to become a teacher, and to find out whether there is an effect of PPLSP and student interest on readiness to become a teacher. The research method used in this study is an explanatory survey method with data collection techniques using questionnaires. Respondents in this study amounted to 96 students from the Office Management Education Study program, Faculty of Education Indonesia, Indonesian Education University Class of 2017 and 2018. Based on the results of the study, information was obtained that PPLSP, student interest, and readiness to become a teacher were in the high category. Then, from the results of hypothesis testing, it was found that PPLSP and student interest had a positive and significant influence on readiness to become a teacher. Thus readiness to become a teacher can be optimized through increasing PPLSP and student interest.